IMPLEMENTASI 4 PILAR KEBANGSAAN DALAM PEMBELAJARAN PKN SEBAGAI PENGUATAN KARAKTER PESERTA DIDIK SEKOLAH DASAR DI ERA MODERN - Priono, Rizka Fadhilah; Annisa , Sofia; Nainggolan , Adellina Ahmad Zain; Siregar, Siti Afifah; Yunita, Sri; Dharma , Surya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Rapid social change accompanied by the expansion of digital technology has affected the moral development and behavioral patterns of children at the elementary school level, making character education increasingly important in today’s educational environment. Civic Education learning is considered capable of introducing and strengthening the principles contained in the Four Pillars of Indonesian Nationality, which consist of Pancasila, the Constitution of 1945, the Republic of Indonesia, and the value of Unity in Diversity. This research was conducted to identify the implementation of the Four Pillars of Nationality within PKn learning as an effort to develop the character of elementary school students amid contemporary societal challenges. A descriptive qualitative method was utilized in this study through a literature review process involving journals, academic books, and various educational references related to citizenship and character education. The results indicate that the integration of national values into classroom learning activities can encourage the growth of positive student characteristics such as nationalism, social responsibility, discipline, tolerance, cooperation, and respect for diversity. In addition, the success of character formation is also influenced by the teacher’s ability to design innovative and meaningful learning experiences that are connected to students’ daily lives. Consequently, the application of the Four Pillars of Nationality in Civic Education learning can become an effective foundation for creating a young generation that possesses integrity, strong national identity, and positive moral values in the modern era.